Meta-analysis on the effect of foraging on feather pecking and feather coverage - Wen, Jiying; Yang, Shenglin; Zhu, Jinjin; Liu, Ai; Rao, Yifu (Applied animal behaviour science, 2025)
Feather pecking (FP) has been a longstanding concern in avian welfare because of its potential to inflict harm on bird plumage. Researchers have proposed the redirection hypothesis in studies investigating factors influencing FP, positing that pecking feathers serve as a redirection of foraging behavior. Following the proposition of this theory, farmers have begun to integrate foraging materials as a tactic to mitigate FP. However, recent studies have suggested that approaches promoting foraging behaviors may not be successful in diminishing FP, thereby questioning the validity of the redirection hypothesis. This study employs meta-analysis to assess the effects of foraging on FP and feather coverage. A comprehensive meta-analysis was performed on 16 studies sourced from three databases. The findings of the meta-analysis comparing foraging and non-foraging groups suggest that foraging can reduce FP and enhance feather coverage. However, subgroup analysis found that digestible foraging materials can effectively reduce FP and increase feather coverage, while promoting foraging activities alone does not lead to a decrease in FP or an increase in feather coverage. •Foraging materials can reduce FP and increase feather coverage.•Simply stimulating foraging activities cannot reduce FP and increase feather coverage.•The content of the redirection hypothesis is worth re examining.